Identification of Sponge-Associated Bacteria with Antibacterial Property against Staphylococcus aureus based on Molecular Approach - Ocky Karna Radjasa (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
Staphylococcus aureus is among human pathogens which are known to be resistant to almost clinically significant antibiotics that causes a crisis, in the treatment and management of infectious disease, and also presents a clear danger to the future of public health. Recently, invertebrate-associated microorganisms have become the target of the search for marine microbial natural products. Sponge-associated microorganisms are one of the most interesting natural product sources because they produce bioactive natural products including polyketides and nonribosomal peptides. Molecular approach based on 16S rDNA has been very successful in the identification and the search of secondary metabolite-producing microorganisms, particularly by using specific degenerated primers, for the detection of Polyketide Synthases (PKS) and Nonribosomal Peptide Synthetases (NRPS) gene fragments that are essential for the biosynthesis of bioactive products. Four bacterial isolates from sponge Dysidea sp. were found to inhibit the growth of S. aureus. However, only the best two isolates were selected for further identification and screening for the presence of either PKS or NRPS. The results revealed that both isolates BSP5.11 and BSP11.7 have 99% homology with Alpha proteobacterium. PCR analysis of PKS and NRPS gene fragments showed that they both amplified the NRPS but not the PKS gene fragments.